2016
DOI: 10.3390/en9080657
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetohydrodynamic Effects on Steam Bubble Formation in Vertical Heated Upward Flow

Abstract: Abstract:In this paper, the modeling of a steady state two phase flow heated through a vertical upward flow under electro-magneto-hydro-dynamic forces is presented. The thermal non-equilibrium, non-homogeneous, two-phase flow model consisting of mass, momentum and energy conservation in each phase has been adjusted for subcooled inlet conditions close to saturation. The P-1 approximation, viscous dissipation and Joule heating are included in the energy equations. It was seen that the Lorentz force can decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The influences of various parameters (such as the viscosity ratio, phase angle, Hall parameter, thermal conductivity ratio, and Prandtl number) on the velocity field, temperature field, shell friction, and Nusselt number were expressed. Mirzaee et al [44] investigated the effects of electromagnetohydrodynamics (EMHD) on the shape of a vapor bubble in upward heated vertical flow. It was observed that the Lorentz force could decrease and delay bubble production.…”
Section: Introductionmentioning
confidence: 99%
“…The influences of various parameters (such as the viscosity ratio, phase angle, Hall parameter, thermal conductivity ratio, and Prandtl number) on the velocity field, temperature field, shell friction, and Nusselt number were expressed. Mirzaee et al [44] investigated the effects of electromagnetohydrodynamics (EMHD) on the shape of a vapor bubble in upward heated vertical flow. It was observed that the Lorentz force could decrease and delay bubble production.…”
Section: Introductionmentioning
confidence: 99%
“…The force balance conditions of the two-liquid model for any stage (i refers to fluid or vapor) in Table 3 can be found in Collier and Thome [3]. Here, the inertial force term in the interfacial momentum exchange model has been combined into single expressions to avoid the use of regime maps [16][17][18]. The Lorentz term considers powers other than weight and trituration powers, for example, magneto-hydrodynamic power.…”
Section: Governing Equationsmentioning
confidence: 99%
“…Recently, Jamalabadi [16][17][18] worked on the EMHD effects on a straight up flow in annular pipe in a two-phase flow regime. However, the effect of MHD and nanoparticles on subcooled vertical pipe flow has not been calculated yet.…”
Section: Introductionmentioning
confidence: 99%
“…One of the institutions in the world where low-speed penetrator technologies are being developed is the Space Research Center (CBK) of the Polish Academy of Sciences. Examples of penetrators with a battery in the form of a capacitor are MUPUS [6] and CHOMIK [7]-a penetrator developed for the Phobos Grunt mission. The driving unit of both penetrators is an electromagnet with a movable dive (hammer), shown in Figure 2.…”
Section: Introductionmentioning
confidence: 99%